Membongkar Agenda Terselubung Fundamentalisme Islam: dari Nalar Arab ke Nalar Pribumi - Ahmad Lutfi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2015)
The Western modernity has emerged reaction from thecommunity of Islam. The reaction appears into three types: fundamentalist,traditionalist, and liberal Islam. The first one is to refer the Qur’ānic text.The second is to imlement all traditions in the Prophet’s era. The last isto refer the Islamic teaching, religious text, and condition they live. Thispaper will provide some corrections to the thought which globalizedfundemantalist it self with Islamic universalism project. This paper will usePost-colonial study approach .